Potential of Essential Oils of Arabica Coffee Beans (Coffea arabica L.) Java Preanger in Aromatherapy Candle Formulations - Handayani, Retty; Hindun, Siti; Aprilian, Salsa; Febriyanti, Raden Maya; Chaerunisaa, Anis Yohana (Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, 2024)
Coffea arabica L. is one of the most widely consumed beverages globally, with extensive research highlighting its significant physical and mental health benefits. However, research has primarily focused on the effects of drinking coffee rather than inhaling its aroma. Aromatherapy, a complementary and alternative medicine, is used to address conditions such as stress, anxiety, depression, insomnia, and pain. Despite the pleasant nature of coffee aroma for many individuals, studies on the therapeutic effects of coffee aroma are limited. This study aimed to develop an aromatherapy candle formulation with potential relaxation and calming properties using coffee oil. The formulations were prepared with varying concentrations of coffee oil: 5%, 10%, 15%, 20%, and 25%. The methodological approach encompassed material collection, coffee bean roasting, Soxhlet extraction of coffee oil, and characterization of the extracted oil. Additionally, the study involved the formulation of aromatherapy candles, followed by comprehensive evaluations, including organoleptic testing, homogeneity assessment, air bubble analysis, melting point determination, burn time measurement, hedonic evaluation, and effectiveness testing. Among the tested formulations, the preparation containing 15% coffee oil (F3) exhibited superior physical properties. Effectiveness testing revealed that 50.00% of panelists experienced relaxation, 23.33% felt refreshed, 16.67% reported a calming effect, and 10.00% felt drowsy.